1997
DOI: 10.1530/eje.0.1370127
|View full text |Cite
|
Sign up to set email alerts
|

Reduced gastric inhibitory polypeptide but normal glucagon-like peptide 1 response to oral glucose in postmenopausal women with impaired glucose tolerance

Abstract: Objective: The gastrointestinal hormones, gastric inhibitory polypeptide (GIP) and glucagon-like peptide 1 (GLP-1), are both released from the gut after oral glucose ingestion and stimulate insulin secretion. This study examined the release of these hormones in subjects with impaired glucose tolerance (IGT), which precedes the development of non-insulin-dependent diabetes. Design and methods: Six postmenopausal women with IGT, aged 59 years, underwent a 75 g oral glucose tolerance test and plasma levels of GIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 35 publications
5
32
1
1
Order By: Relevance
“…Another explanation for the higher GLP-1 response after oral glucose vs the solid mixed meal would be an accelerated gastric emptying that has been described for early diabetic patients during a liquid meal (38,39). In line with earlier studies, GLP-1 response among persons with IH was unaltered (7,8,10,40,41). This suggests that a defect in GLP-1 secretion is unlikely to precede type 2 diabetes development, which is consistent with earlier findings among first-degree diabetes relatives, and in induced insulin resistance among healthy subjects (27,42).…”
Section: Figure 1 Glucose Insulin and Triglyceride Responses (Meangssupporting
confidence: 90%
See 1 more Smart Citation
“…Another explanation for the higher GLP-1 response after oral glucose vs the solid mixed meal would be an accelerated gastric emptying that has been described for early diabetic patients during a liquid meal (38,39). In line with earlier studies, GLP-1 response among persons with IH was unaltered (7,8,10,40,41). This suggests that a defect in GLP-1 secretion is unlikely to precede type 2 diabetes development, which is consistent with earlier findings among first-degree diabetes relatives, and in induced insulin resistance among healthy subjects (27,42).…”
Section: Figure 1 Glucose Insulin and Triglyceride Responses (Meangssupporting
confidence: 90%
“…Earlier studies among diabetic patients mostly report no change in GIP response after a meal or oral glucose (10,11,12,13), a higher response (7, 9, 41) or a slightly lower response (8,44). Similarly, GIP response among persons with IH has been reported unaltered (8,41), decreased (40) or increased (7). Obesity has been reported to be associated with higher GIP responses (43), but we did not find a relationship between BMI and GIP meal response.…”
Section: Figure 1 Glucose Insulin and Triglyceride Responses (Meangscontrasting
confidence: 81%
“…Normal GLP-1 responses were reported in some subjects with impaired glucose tolerance [96,106], whereas an impairment was identified in others. However, further analysis concluded that the reductions could largely be explained by differences in BMI and/or insulin sensitivity [93,107].…”
Section: Subjects At Risk Of Developing Type 2 Diabetesmentioning
confidence: 99%
“…Disturbance of incretin secretion may also be present in insulin-resistant states, because a reduced GIP response after an oral glucose tolerance test has been demonstrated in middle-aged women with IGT (8). Furthermore, a reduced GLP-1 response after food intake occurs in obese individuals (9).…”
mentioning
confidence: 99%